Prácticas de mejora para el proceso de acompañamiento pedagógico - San Martín Cantero, Daniel; San Martín Aedo, Reina; Pérez Morales, Sergio; Bórquez Mella, Jessica (Universidad de Costa Rica, 2021)
This article is derived from a research project on accompaniment experiences experienced by pedagogy students in their final professional practice in the region of La Araucanía, Chile. It was developed during the 2018-2019 period by researchers from the Catholic University of Temuco. The purpose was to describe problems and criteria for improvement during the accompaniment in the initial teacher training. The antecedents place the accompaniment as a learning experience that can be problematic for students who do not have a timely pedagogical orientation. The qualitative method was used and 15 pedagogical boarding students were interviewed. The interviews were coded according to the Grounded Theory approach. The results were categories associated with university management, tutor-student relationship and sociocultural characteristics as problems in the accompaniment. In addition, criteria are set out to improve pedagogical support related to the selection of tutors and mentors and incentives to recognize their work. By way of conclusion, there is an artisanal status of the accompaniment, which generates helplessness in students. In this way, training demands are revealed that are contrary to the needs of pedagogical practice centers. The importance of articulating universities and practice centers to rethink the roles of tutors and students is made visible. Consequently, it is recommended to design a tutor profile that represents the interests of the educational community to reduce the gap between theory and practice.